Figure Skating's Greatest stars - Milton, Steve (Richmomd Hill, Ont. : Firefly Books, 2009)
Presents the finest of skating's four Olympic disciplines: men's singles, women's singles, pairs and ice dancing.
Greatest stars and leading legends -- The men -- Figures and 6.0 -- The women -- Nationalism and the building of champions -- The pairs -- Pivotal moments -- The dancers -- Legends in the making.
Includes bibliographical references (p. 217) and index.
Sports
Keywords: Figure skaters -- Biography; Figure skating; Patineurs artistiques -- Biographies; Patinage artistique